High-capacity sodium-ion battery positive electrode material as well as preparation method and application thereof

By doping Co and Ti elements into the O3-phase nickel-ferromanganese-based positive electrode material, the sodium ion battery positive electrode material with NaNixFeyMnzCoaTibO2 structure was prepared, and the problem of poor capacity attenuation and stability of the sodium ion battery positive electrode material in the prior art was solved, and high Electrochemical performance improvements in capacity and long life.

CN119208583APending Publication Date: 2024-12-27TIANJIN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411214394.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-31
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode materials have fast capacity decayed during charging and discharging, poor cycle stability, and the prior art is difficult to effectively improve their specific capacity and electrochemical properties.

Method used

Based on O3-phase nickel-ferromanganese-based positive electrode material, doping active Co elements and inactive Ti elements, it is prepared by mixing precursor materials with Na, Ni, Fe, Mn, Co and Ti for high-temperature calcination to form the high-level structure of NaNixFeyMnzCoaTibO2. Capacity sodium ion battery positive electrode material.

Benefits of technology

The high specific capacity and long life of sodium ion batteries are achieved (cycle stability), and the preparation method is simplified, with potential industrial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208583A_ABST
    Figure CN119208583A_ABST
Patent Text Reader

Abstract

The invention discloses a high-capacity sodium ion battery positive electrode material and a preparation method and application thereof.The preparation method comprises the steps that a Na source, a Ni source, a Fe source, a Mn source, a Co source and a Ti source are evenly mixed, and a precursor material is obtained; and calcining the precursor material at high temperature, and cooling along with a furnace to obtain the high-capacity sodium-ion battery positive electrode material. Ni, Fe and Mn are used as a basic framework, Ni and Fe are active elements and contribute capacity through valence change, Mn is an inactive element and is mainly used for stabilizing a phase lattice structure, and an active Co element and an inactive Ti element are co-doped on a nickel-iron-manganese-based layered oxide, so that the performance of the nickel-iron-manganese-based layered oxide is improved. The active element Co and the inactive element Ti are co-doped synergistically to inhibit the adverse phase change of the nickel-iron-manganese-based layered oxide in electrochemical reaction, so that the sodium-ion battery prepared from the high-capacity sodium-ion battery positive electrode material has the advantages of high specific capacity, long service life and the like, and has potential application prospects in the sodium-ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a high-capacity sodium ion battery positive electrode material and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries have abundant sodium resources, low cost and reliable safety, and have great potential in the next generation of energy storage devices. As the key, cathode materials play a vital role in realizing high energy density sodium-ion batteries. Among various cathode materials, layered transition metal oxides have attracted widespread attention due to their high voltage platform, high capacity and easy synthesis. According to the different Na coordination environment and oxygen stacking sequence, layered transition metal oxides can be divided into two types: P2 (ABBA stacking sequence) and O3 (ABCABC stacking sequence), that is, Na occupies triangular prism and octahedral sites respectively. Since the sodium ions in the O3-type cathode material are located in the octahedral sites between the transition metal layers, the sodium ions need to overcome a large energy barrier to move from one octahedral site to another, and it will also cause the slip of the transition metal layer. Therefore, the sodium ions are easily affected by transition metals at different positions during the diffusion process. Although layered oxide cathode materials have high specific capacity, compared with the cathode materials of lithium-ion batteries, there is still a long way to go to further improve the specific capacity of sodium-ion battery cathode materials, which is a key technical problem that needs to be solved in the development of high specific energy sodium-ion batteries. Especially for layered oxide sodium-ion battery positive electrode materials, they need to undergo complex structural evolution during the charge and discharge process, which usually causes the capacity of the material to decay too quickly and have poor cycle stability.

[0003] The Chinese patent document with publication number CN115241450A discloses a sodium ion battery positive electrode material and its preparation and application. 0.3 Fe 0.4 Mn 0.3 F x O (2-x) The rate performance and cycle stability of the positive electrode material are improved by replacing O with F at a molar ratio of 0.05-0.1. However, the electrochemical performance of the positive electrode material needs to be improved, whether in terms of specific capacity (discharge capacity up to 112.42 mAh / g at 0.2C) or cycle stability (capacity retention rate up to 92.36% after 40 cycles).

[0004] The Chinese patent document with publication number CN115692684A discloses a multi-component composite positive electrode material and a preparation method and a battery thereof, wherein Na x Ni y Fe z Mn u Bi vCs w O 2 The experimental operation of composite positive electrode materials is complicated, and the Bi and Cs elements are not environmentally friendly, which is not conducive to widespread application.

[0005] Therefore, the development of sodium-ion battery cathode materials with higher specific capacity and excellent cycle stability is of great significance to promote the industrial application of sodium-ion batteries. However, the existing technology still needs to be improved and enhanced. Summary of the invention

[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide a high-capacity sodium ion battery positive electrode material, which is based on an O3 phase nickel-iron-manganese-based positive electrode material and is doped with an active Co element and an inactive Ti element.

[0007] Another object of the present invention is to provide a method for preparing the above-mentioned high-capacity sodium ion battery positive electrode material.

[0008] Another object of the present invention is to provide an application of the high-capacity sodium ion battery positive electrode material in a sodium ion battery.

[0009] The purpose of the present invention is achieved through the following technical solutions.

[0010] A high-capacity sodium-ion battery cathode material, the general structural formula of which is NaNi x Fe y Mn z Co a Ti b O 2 , where 0.2≤x≤0.3, 0.1≤y≤0.3, 0.4≤z≤0.5, 0 <a≤0.1,0<b≤0.1,x+y+z+a+b=1。

[0011] Preferably, 0.25≤x≤0.3, 0.15≤y≤0.3, 0.4≤z≤0.5, 0 <a≤0.1,0<b≤0.1,x+y+z+a+b=1。

[0012] As a further preferred embodiment, 0.25≤x≤0.27, 0.25≤y≤0.27, 0.4≤z≤0.5, 0 <a≤0.03,0<b≤0.03,x+y+z+a+b=1。

[0013] Most preferably, x=0.27, y=0.27, z=0.4, and a=b=0.03.

[0014] The method for preparing the above-mentioned high-capacity sodium ion battery positive electrode material comprises the following steps:

[0015] Step 1, mixing Na source, Ni source, Fe source, Mn source, Co source and Ti source uniformly to obtain a precursor material, wherein the ratio of Na in Na source, Ni in Ni source, Fe in Fe source, Mn in Mn source, Co in Co source and Ti in Ti source is 1.05:x:y:z:a:b according to the amount of substances;

[0016] In step 1, the Na source is one or a mixture of sodium acetate, sodium carbonate, sodium bicarbonate, sodium nitrate and sodium hydroxide.

[0017] In step 1, the Ni source is one or a mixture of Ni oxide, Ni chloride, Ni hydroxide, Ni acetylacetonate, Ni ethanolate and Ni nitrate.

[0018] In step 1, the Fe source is one or a mixture of several of Fe oxide, Fe chloride, Fe hydroxide, Fe acetylacetonate, Fe ethanolate and Fe nitrate.

[0019] In step 1, the Mn source is one or a mixture of Mn oxide, Mn chloride, Mn hydroxide, Mn acetylacetonate, Mn ethanolate and Mn nitrate.

[0020] In step 1, the Co source is one or a mixture of Co oxide, Co chloride, Co hydroxide, Co acetylacetonate, Co ethanolate and Co nitrate.

[0021] In step 1, the Ti source is one or a mixture of Ti oxide, Ti chloride, Ti hydroxide, Ti acetylacetonate, Ti ethanolate and Ti nitrate.

[0022] In step 1, the method of uniformly mixing the Na source, the Ni source, the Fe source, the Mn source, the Co source and the Ti source is one of dry ball milling, wet ball milling, spray drying and sol-gel method.

[0023] In the above technical solution, the rotation speed of the wet ball mill is 1500-2000 rpm, and the time of the wet ball mill is 2-3 hours.

[0024] Step 2, calcining the precursor material at a high temperature of 850-950° C. for 12-14 hours, cooling the furnace, and obtaining a high-capacity sodium ion battery positive electrode material.

[0025] In step 2, the heating rate to 850-950° C. is 4-6° C. / min.

[0026] The application of the above-mentioned sodium ion battery positive electrode material in improving the discharge specific capacity of the sodium ion battery.

[0027] In the above technical solution, the sodium ion battery includes a liquid sodium ion battery and a solid sodium ion battery.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. The present invention takes Ni, Fe and Mn as the basic framework, wherein Ni and Fe are active elements that contribute to capacity through their valence changes, while Mn is an inactive element that is mainly used to stabilize the phase lattice structure. Active Co element and inactive Ti element are co-doped on the nickel-iron-manganese-based layered oxide. The synergistic co-doping of active element Co and inactive element Ti inhibits the adverse phase change of the nickel-iron-manganese-based layered oxide in the electrochemical reaction, so that the sodium ion battery prepared by the high-capacity sodium ion battery positive electrode material of the present invention has the advantages of high specific capacity, long life (cycle stability), etc., and has potential application prospects in sodium ion batteries.

[0030] 2. The preparation method of the present invention is simple. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 XRD patterns of the high-capacity sodium ion battery positive electrode materials prepared in Examples 1 to 5;

[0032] FIG2 is a SEM of the high-capacity sodium ion battery positive electrode material prepared in Examples 1 to 5, wherein: Figure 2(a) to Figure 2(e) The SEM images of the high-capacity sodium ion battery positive electrode materials prepared in Examples 1 to 5 are shown in sequence;

[0033] Figure 3 The charge and discharge curves of the sodium ion batteries of Examples 6 to 10 at 0.2C;

[0034] Figure 4 The cycle performance diagram of the sodium ion battery of Examples 6 to 10 at 1C;

[0035] Figure 5 XRD patterns of the high-capacity sodium ion battery positive electrode materials prepared in Comparative Examples 1 to 3;

[0036] FIG6 is a SEM of the high-capacity sodium ion battery positive electrode material prepared in Comparative Examples 1 to 3, wherein: Figure 6(a) to Figure 6(c) The SEM images of the high-capacity sodium ion battery positive electrode materials prepared in Comparative Examples 1 to 3 are shown in sequence;

[0037] Figure 7 The charge and discharge curves of the sodium ion batteries of Comparative Examples 4 to 6 at 0.2C;

[0038] Figure 8 This is a cycle performance diagram of the sodium ion batteries of Comparative Examples 4 to 6 at 1C. DETAILED DESCRIPTION

[0039] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0040] The raw material information involved in the following examples is as follows:

[0041] Drug Name Model(Purity) Manufacturer Sodium carbonate Analytical grade Shanghai Aladdin Biochemical Technology Co., Ltd. <![CDATA[Manganese(III) oxide (Mn 2 O 3 )]]> Analytical grade Tianjin Fuchen Company Nickel Oxide (NiO) Analytical grade Shanghai MacLean Biochemical Technology Co., Ltd. <![CDATA[Iron(III) oxide (Fe 2 O 3 )]]> Analytical grade Shanghai Aladdin Biochemical Technology Co., Ltd. <![CDATA[Titanium dioxide (TiO 2 )]]> Analytical grade Shanghai Aladdin Biochemical Technology Co., Ltd. <![CDATA[Cobalt(II,III) oxide (Co 3 O 4 )]]> Analytical grade Shanghai Aladdin Biochemical Technology Co., Ltd. N-Methylpyrrolidone 99% Tianjin Fuchen Company Acetylene Black Chemically pure Tianjin Fuchen Company Polyvinylidene fluoride Analytical grade Shenzhen Kejing Zhida Technology Co., Ltd. Electrolyte Battery Level Duoduo Reagent

[0042] The various performance indicators in the following examples are strictly measured using precise instruments or standard test methods:

[0043] The XRD pattern (crystal structure of the sample) was measured by an X-ray diffractometer (ARL EQUINOX 3000, Thermo Fisher Scientific) at 40 kV and 40 mA in the 2θ range of 10 to 80°.

[0044] The surface morphology of the material was characterized by using a Quanta FEG 250 field emission scanning electron microscope and a Verios 460L ultra-high resolution field emission scanning electron microscope from FEI Company of the United States.

[0045] On the LAND system (LAND CT2001A, China), at 2.0-4.2 V (vs. Na / Na + ) potential window for constant current charge and discharge measurements and cycle performance tests.

[0046] Embodiments 1 to 5

[0047] A method for preparing a high-capacity sodium ion battery positive electrode material comprises the following steps:

[0048] Step 1, mixing Na source, Ni source, Fe source, Mn source, Co source and Ti source in a ball mill, high-speed ball milling at a speed of 1800 rpm for 2 h until uniform (wet ball milling, ball milling aid is acetone), and drying in a vacuum oven at 80 ° C for 12 h to obtain a precursor material, wherein the ratio of Na in the Na source, Ni in the Ni source, Fe in the Fe source, Mn in the Mn source, Co in the Co source and Ti in the Ti source is X, and the value of X is shown in Table 1, the Na source is sodium carbonate, the Ni source is Ni oxide (NiO), the Fe source is Fe oxide (Fe 2 O 3 ), the Mn source is Mn oxide (Mn 2 O 3 ), the Co source is Co oxide (Co 3 O 4 ), the Ti source is Ti oxide (TiO 2 );

[0049] Step 2: transfer the precursor material to a muffle furnace, heat it to 900°C at a heating rate of 5°C / min under air atmosphere, calcine it at 900°C for 12h, and cool it in the furnace to obtain a high-capacity sodium ion battery positive electrode material.

[0050] In Examples 1 to 5, the doping amounts of Co and Ti are not high and will not change the O3 phase structure of the material.

[0051] Table 1

[0052] Example X serial number Example 1 1.05:0.27:0.18:0.45:0.05:0.05 <![CDATA[NaNi 0.27 Feb 0.18 Mr 0.45 Co 0.05 Tea 0.05 O 2 ]]> Example 2 1.05:0.25:0.25:0.4:0.05:0.05 <![CDATA[NaNi 0.25 Feb 0.25 Mr 0.4 Co 0.05 Tea 0.05 O 2 ]]> Example 3 1.05:0.285:0.19:0.475:0.025:0.025 <![CDATA[NaNi 0.285 Feb 0.19 Mr 0.475 Co 0.025 Tea 0.025 O 2 ]]> Example 4 1.05:0.27:0.27:0.4:0.03:0.03 <![CDATA[NaNi 0.27 Feb 0.27 Mr 0.4 Co 0.03 Tea 0.03 O 2 ]]> Example 5 1.05:0.3:0.18:0.45:0.02:0.05 <![CDATA[NaNi 0.3 Feb 0.18 Mr 0.45 Co 0.02 Tea 0.05 O 2 ]]>

[0053] Comparative Example 1

[0054] A high-capacity sodium-ion battery cathode material (NaNi 0.3 Fe 0.2 Mn 0.5 O 2 ), comprising the following steps:

[0055] Step 1, mixing Na source, Ni source, Fe source and Mn source in a ball mill, and high-speed ball milling at a speed of 1800 rpm for 2 hours until uniform (wet ball milling, ball milling aid is acetone), to obtain a precursor material, in which the ratio of Na in the Na source, Ni in the Ni source, Fe in the Fe source and Mn in the Mn source is 1.05:0.3:0.2:0.5 in terms of the amount of substance, the Na source is sodium carbonate, the Ni source is Ni oxide (NiO), the Fe source is Fe oxide (Fe 2 O 3 ), the Mn source is Mn oxide (Mn 2 O 3 );

[0056] Step 2: transfer the precursor material to a muffle furnace, heat it to 900°C at a heating rate of 5°C / min under air atmosphere, calcine it at 900°C for 12h, and cool it in the furnace to obtain a high-capacity sodium ion battery positive electrode material.

[0057] Comparative Example 2

[0058] A high-capacity sodium-ion battery cathode material (NaNi 0.3 Fe 0.2 Mn 0.45 Ti 0.05 O 2 ), comprising the following steps:

[0059] Step 1, mixing Na source, Ni source, Fe source, Mn source and Ti source in a ball mill, high-speed ball milling at a speed of 1800 rpm for 2 hours until uniform (wet ball milling, ball milling aid is acetone), and drying in a vacuum oven at 80° C. for 12 hours to obtain a precursor material, wherein the ratio of Na in the Na source, Ni in the Ni source, Fe in the Fe source, Mn in the Mn source and Ti in the Ti source is 1.05:0.3:0.2:0.45:0.05 in terms of the amount of substance, the Na source is sodium carbonate, the Ni source is Ni oxide (NiO), the Fe source is Fe oxide (Fe 2 O 3 ), the Mn source is Mn oxide (Mn 2 O 3 ), the Ti source is Ti oxide (TiO 2 );

[0060] Step 2: transfer the precursor material to a muffle furnace, heat it to 900°C at a heating rate of 5°C / min under air atmosphere, calcine it at 900°C for 12h, and cool it in the furnace to obtain a high-capacity sodium ion battery positive electrode material.

[0061] Comparative Example 3

[0062] A high-capacity sodium-ion battery cathode material (NaNi 0.3 Fe 0.15 Mn 0.5 Co 0.05 O 2 ), comprising the following steps:

[0063] Step 1, mixing Na source, Ni source, Fe source, Mn source and Co source in a ball mill, high-speed ball milling at a speed of 1800 rpm for 2 hours until uniform (wet ball milling, ball milling aid is acetone), and drying in a vacuum oven at 80° C. for 12 hours to obtain a precursor material, wherein the ratio of Na in the Na source, Ni in the Ni source, Fe in the Fe source, Mn in the Mn source and Co in the Co source is 1.05:0.3:0.15:0.5:0.05 in terms of the amount of substance, the Na source is sodium carbonate, the Ni source is Ni oxide (NiO), the Fe source is Fe oxide (Fe 2 O 3 ), the Mn source is Mn oxide (Mn 2 O 3 ), the Co source is Co oxide (Co 3 O 4 );

[0064] Step 2: transfer the precursor material to a muffle furnace, heat it to 900°C at a heating rate of 5°C / min under air atmosphere, calcine it at 900°C for 12h, and cool it in the furnace to obtain a high-capacity sodium ion battery positive electrode material.

[0065] Examples 6 to 10 and Comparative Examples 4 to 6

[0066] A method for preparing a sodium ion battery, comprising: in a glove box, assembling a positive electrode shell, a positive electrode sheet, a diaphragm, a negative electrode sheet, a gasket, a spring sheet, and a negative electrode shell in order to obtain a sodium ion battery, wherein the electrolyte in the electrolyte solution used is NaClO 4 The concentration of electrolyte in the electrolyte is 1 mol L -1 The solvents in the electrolyte are propylene carbonate (PC) and fluoroethylene carbonate (FEC), and the ratio of propylene carbonate to fluoroethylene carbonate is 95:5 by volume. The negative electrode sheet is a sodium sheet, and the separator is a glass fiber. The method for obtaining the positive electrode sheet is: mixing the positive electrode material, the conductive agent (acetylene black) and the binder solution (the binder solution is a mixture of polyvinylidene fluoride (PVDF) and N-methylpyrrolidone, and the concentration of polyvinylidene fluoride (PVDF) in the binder solution is 20 mg mL -1 , by mass fraction, the ratio of polyvinylidene fluoride (PVDF) in the positive electrode material, conductive agent and binder solution is 8:1:1), put it into an agate mortar and grind it for 30 minutes until it is uniform, and obtain a slurry. The slurry is evenly coated on a carbon-containing aluminum foil as a current collector with a 150-micron scraper, and dried in a vacuum oven at 80°C for 12 hours to fully volatilize N-methylpyrrolidone (NMP). When the temperature drops to room temperature, take it out, cut out a circular electrode sheet with a diameter of 12 mm with a sheet cutter, and then use a sheet press to press the circular electrode sheet at a pressure of 10 MPa for 30 seconds to obtain a positive electrode sheet with a diameter of 12 mm (the positive electrode material loading on the positive electrode sheet is 1-1.3 mg). The positive electrode material is one of the high-capacity sodium ion battery positive electrode materials prepared in Examples 1 to 5 and Comparative Examples 1 to 3.

[0067] Table 2

[0068] Examples and Comparative Examples Preparation of positive electrode materials for sodium ion batteries Example 6 Example 1 Example 7 Example 2 Example 8 Example 3 Example 9 Example 4 Example 10 Example 5 Comparative Example 4 Comparative Example 1 Comparative Example 5 Comparative Example 2 Comparative Example 6 Comparative Example 3

[0069] The XRD patterns of the high-capacity sodium ion battery positive electrode materials prepared in Examples 1 to 5 are as follows: Figure 1 As shown, after XRD analysis, Figure 1 The diffraction peak intensity of the high-capacity sodium ion battery positive electrode material prepared in Examples 1 to 5 is relatively high, indicating that it has good crystallinity, is indistinguishable from the standard card PDF-54-0887, and has the characteristic peak of the triclinic R3m space group, indicating that the high-capacity sodium ion battery positive electrode material prepared in Examples 1 to 5 is O3 phase.

[0070] The SEM image of the high-capacity sodium ion battery positive electrode material prepared in Example 1 is shown in Figure 2(a), the SEM image of the high-capacity sodium ion battery positive electrode material prepared in Example 2 is shown in Figure 2(b), the SEM image of the high-capacity sodium ion battery positive electrode material prepared in Example 3 is shown in Figure 2(c), the SEM image of the high-capacity sodium ion battery positive electrode material prepared in Example 4 is shown in Figure 2(d), and the SEM image of the high-capacity sodium ion battery positive electrode material prepared in Example 5 is shown in Figure 2(e). The high-capacity sodium ion battery positive electrode materials prepared in Examples 1 to 5 are typical layered structures with relatively uniform particle size distribution.

[0071] The charge and discharge curves of the sodium ion battery prepared from the high-capacity sodium ion battery positive electrode materials of Examples 1 to 5 are as follows: Figure 3 As shown in Figure 2, at 2.0-4.2V, 0.2C, the discharge specific capacity of the sodium ion battery prepared from the high-capacity sodium ion battery positive electrode material of Example 1 is 151.8 mAh g -1 The discharge capacity of the sodium ion battery prepared by the high-capacity sodium ion battery positive electrode material of Example 2 is 138.97 mAh g -1 The discharge capacity of the sodium ion battery prepared by the high-capacity sodium ion battery positive electrode material of Example 3 is 142.69 mAh g -1 The discharge capacity of the sodium ion battery prepared by the high-capacity sodium ion battery positive electrode material of Example 4 is 171.74 mAh g -1 The discharge capacity of the sodium ion battery prepared by the high-capacity sodium ion battery positive electrode material of Example 5 is 148.99 mAh g -1 .

[0072] The cycle performance of the sodium ion battery prepared from the high-capacity sodium ion battery positive electrode materials of Examples 1 to 5 is shown in FIG. Figure 4 As shown in Figure 2, at 2.0-4.2 V and 1 C current density, the initial capacity of the sodium ion battery prepared from the high-capacity sodium ion battery positive electrode material of Example 1 is 133.59 mAh g -1 After 100 cycles, the discharge capacity is 115.32 mAh g -1 The capacity retention rate is 86.32%. The initial capacity of the sodium ion battery prepared by the high-capacity sodium ion battery positive electrode material of Example 2 is 122.16 mAh g -1 After 100 cycles, the discharge capacity is 109.42 mAh g -1 The capacity retention rate is 89.57%; the initial capacity of the sodium ion battery prepared by the high-capacity sodium ion battery positive electrode material of Example 3 is 123.54 mAh g -1 After 100 cycles, the discharge capacity is 100.75 mAh g-1 The capacity retention rate is 81.55%; the initial capacity of the sodium ion battery prepared by the high-capacity sodium ion battery positive electrode material of Example 4 is 149.56 mAh g -1 After 100 cycles, the discharge capacity is 111.13 mAh g -1 The capacity retention rate is 74.30%; the initial capacity of the sodium ion battery prepared by the high-capacity sodium ion battery positive electrode material of Example 5 is 127.98 mAh g -1 After 100 cycles, the discharge capacity is 108.25 mAh g -1 The capacity retention rate was 84.58%.

[0073] The XRD patterns of the high-capacity sodium ion battery positive electrode materials prepared in Comparative Examples 1 to 3 are as follows: Figure 5 As shown, after XRD analysis, Figure 5 The diffraction peak intensity of the high-capacity sodium ion battery positive electrode material prepared in Comparative Examples 1 to 3 is relatively high, indicating that it has good crystallinity, which is no different from the standard card PDF#54-0887, and has the characteristic peak of the triclinic R3m space group, indicating that the high-capacity sodium ion battery positive electrode material prepared in Comparative Examples 1 to 3 is O3 phase.

[0074] The SEM image of the high-capacity sodium ion battery positive electrode material prepared in Comparative Example 1 is shown in Figure 6(a), the SEM image of the high-capacity sodium ion battery positive electrode material prepared in Comparative Example 2 is shown in Figure 6(b), and the SEM image of the high-capacity sodium ion battery positive electrode material prepared in Comparative Example 3 is shown in Figure 6(c). The high-capacity sodium ion battery positive electrode materials prepared in Comparative Examples 1 to 3 are typical layered structures with relatively uniform particle size distribution.

[0075] The charge and discharge curves of the sodium ion battery prepared from the high-capacity sodium ion battery positive electrode materials of Comparative Examples 1 to 3 are as follows: Figure 7 As shown in Figure 2, at 2.0-4.2V and 0.2C, the discharge capacity of the sodium ion battery prepared from the high-capacity sodium ion battery positive electrode material of Comparative Example 1 is 129.08 mAh g -1 The discharge capacity of the sodium ion battery prepared by the high-capacity sodium ion battery positive electrode material of Comparative Example 2 is 142.31 mAh g -1 The discharge capacity of the sodium ion battery prepared by the high-capacity sodium ion battery positive electrode material of Comparative Example 3 is 135.55 mAh g -1 .

[0076] The cycle performance diagram of the sodium ion battery prepared by the high-capacity sodium ion battery positive electrode materials of Comparative Examples 1 to 3 is as follows Figure 8As shown in Figure 2, at 2.0-4.2V and 1C current density, the initial capacity of the sodium ion battery prepared from the high-capacity sodium ion battery positive electrode material of Comparative Example 1 is 120.53mAh g -1 After 100 cycles, the discharge capacity is 77.44 mAh g -1 The capacity retention rate of the sodium ion battery prepared in Comparative Example 1 after 100 cycles is 64.24%; the initial capacity of the sodium ion battery prepared from the high-capacity sodium ion battery positive electrode material in Comparative Example 2 is 119.04 mAh g -1 After 100 cycles, the discharge capacity is 85.04 mAh g -1 The capacity retention rate of the sodium ion battery prepared in Comparative Example 2 after 100 cycles was 71.43%; the initial capacity of the sodium ion battery prepared from the high-capacity sodium ion battery positive electrode material in Comparative Example 3 was 132.70 mAh g -1 After 100 cycles, the discharge capacity is 97.47 mAh g -1 The capacity retention rate of the sodium ion battery prepared in comparative example 3 after 100 cycles is 73.45%.

[0077] The electrochemical test results show that the discharge capacity and energy density of the embodiments are higher than those of the comparative examples, among which the discharge capacity of the sodium ion battery prepared by the high-capacity sodium ion battery positive electrode material of Example 4 is the highest, which proves that the synergistic effect of the co-doping of Co and Ti elements in a suitable ratio makes the discharge capacity and cycle stability of the sodium ion battery improved simultaneously. The overall performance tests of Examples 6 to 10 and Comparative Examples 4 to 6 are shown in Table 3.

[0078] Table 3 (Charge specific capacity and discharge specific capacity are obtained from charge and discharge measurements, and cycle stability (capacity retention rate) is obtained from cycle performance tests)

[0079]

[0080] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. A high-capacity sodium-ion battery cathode material, the general structural formula of which is NaNi x Fe y Mn z Co a Ti b O2, where 0.2≤x≤0.3,0.1≤y≤0.3,0.4≤z≤0.5,0 <a≤0.1,0<b≤0.1,x+y+z+a+b=1。 2. The method for preparing a high-capacity sodium ion battery positive electrode material according to claim 1, characterized in that: The following steps are involved: Step 1, mixing Na source, Ni source, Fe source, Mn source, Co source and Ti source uniformly to obtain a precursor material, wherein the ratio of Na in Na source, Ni in Ni source, Fe in Fe source, Mn in Mn source, Co in Co source and Ti in Ti source is 1.05:x:y:z:a:b according to the amount of substances; Step 2, calcining the precursor material at a high temperature of 850-950° C. for 12-14 hours, cooling the furnace, and obtaining a high-capacity sodium ion battery positive electrode material.

3. The preparation method according to claim 2, characterized in that: In step 1, the Na source is one or a mixture of sodium acetate, sodium carbonate, sodium bicarbonate, sodium nitrate and sodium hydroxide.

4. The preparation method according to claim 3, characterized in that: In step 1, the Ni source is one or a mixture of Ni oxide, Ni chloride, Ni hydroxide, Ni acetylacetonate, Ni ethanolate and Ni nitrate.

5. The preparation method according to claim 4, characterized in that: In step 1, the Fe source is one or a mixture of several of Fe oxide, Fe chloride, Fe hydroxide, Fe acetylacetonate, Fe ethanolate and Fe nitrate.

6. The preparation method according to claim 5, characterized in that: In step 1, the Mn source is one or a mixture of Mn oxide, Mn chloride, Mn hydroxide, Mn acetylacetonate, Mn ethanolate and Mn nitrate.

7. The preparation method according to claim 6, characterized in that: In step 1, the Co source is one or a mixture of Co oxide, Co chloride, Co hydroxide, Co acetylacetonate, Co ethanolate and Co nitrate; in step 1, the Ti source is one or a mixture of Ti oxide, Ti chloride, Ti hydroxide, Ti acetylacetonate, Ti ethanolate and Ti nitrate.

8. The preparation method according to claim 7, characterized in that: In step 1, the method of uniformly mixing the Na source, the Ni source, the Fe source, the Mn source, the Co source and the Ti source is one of dry ball milling, wet ball milling, spray drying and sol-gel method.

9. The preparation method according to claim 8, characterized in that: The rotation speed of the wet ball mill is 1500-2000 rpm, and the time of the wet ball mill is 2-3 hours.

10. The use of the high-capacity sodium ion battery positive electrode material as described in claim 1 in improving the discharge specific capacity of the sodium ion battery.